FRI0236 Efficacy and safety of tocilizumab therapy in rheumatoid arthritis: prevalence and predictive factors of sustained remission. (23rd January 2014) - Tanaka, H.; Kanazawa, M.; Kawakami, T.; Kido, K.; Kifune, M.; Kubo, M.; Tamimoto, Y.; Tokitou, T.; Tokushige, A.; Nibu, K.; Miyazaki, N.; Mitasato, H.; et al.
Abstract : Background: Clinical remission is now a realistic goal in managing rheumatoid arthritis (RA) following the introduction of biologic agents. A recent study showed that induction and sustained maintenance of clinical remission is associated with less radiographic damage. Tocilizumab (TCZ) is a new biologic disease-modifying antirheumatic drug directed against the activity of IL-6, a key pro-inflammatory cytokine in the pathogenesis of RA. Studies have been shown rapid and sustained efficacy with an acceptable tolerability profile in patients with active RA despite MTX therapy, but there is limited data on sustained remission. Objectives: To study the efficacy and safety of TCZ in RA patients and to examine prevalence and predictive factors of sustained remission. Methods: Seventy-five RA patients receiving TCZ at multiple sites in Yamaguchi prefecture were retrospectively evaluated. The male/female ratio of the subjects was 11/64. The mean age was 58.6 years, and the mean duration of illness was 9.9 years. Mean baseline DAS28-ESR was 5.0 ± 1.2, and 62.7% of the patients had been treated with TNF inhibitors in the past. 34% of the patients were Stage 1 or 2, 76% were Class 1 or 2. 69.3% were concomitantly receiving MTX (mean dose: 7.1 mg/week) and 82.7% were concomitantly receiving PSL (mean dose: 5.0 mg/day). Efficacy was evaluated based on DAS28-ESR scores using the LOCF technique. Remission was defined by DAS28 of <2.6 and according to the ACR/EULAR (Boolean) definition. Sustained remission was defined if DAS28 was <2.6 at 12, 24, 48, and 96 week follow ups. Predictors for sustained remission were identified by logistic regression analyses. Results: The proportion of patients continuing treatment at 96 weeks was 76.5%. The average DAS28-ESR was significantly improved to 2.5 ± 1.4 in 96 weeks. Biologics naïve patients showed a rapid improvement compared with those who switched from TNF inhibitors, although no significant difference was observed. Controlling for baseline characteristics, those who received TCZ/MTX combination did not significantly differ in change in DAS28-ESR, compared with those who received TCZ alone. 60% of the patients achieved DAS28 remission and 28% achieved ACR/EULAR remission at 96 weeks. Overall, 50% of the patients achieved sustained remission. Of those in remission at 12 weeks and 24 weeks, 75.8% and 100%, respectively, achieved sustained remission. Factors that contribute to sustained remission identified by a univariate analysis included shorter disease duration and a lower DAS28-ESR at baseline, as well as a lower DAS28-ESR and achievement of TJC, SJC and CRP of ≤1 at 12 weeks. Conclusions: Based on high remission induction rates and long-term sustained remission provided by TCZ, it was suggested that early therapeutic intervention and favorable treatment response at 12 weeks may contribute to maintenance of remission. References: Nishimoto N, et al., Mod Rheumatol. 2009;19(1):12-9. Maini RN, et al., Arthritis Rheum. 2006 Sep;54(9):2817-29. Disclosure of Interest : None Declared